Pengaruh Pemberian Enzim Papain dan Pakan Tambahan pada Pemeliharaan Ikan Gurami (Osphronemus gouramy) di Air Gambut - Muhamad Noor Yasin; Ummi Suraya (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2022)
The purpose of this was to find out the optimal administration of papain enzyme and supplementary feed in feed, to the survival and growth of gourami fish (Osphronemus gouramy). This research was conducted at the Palangka Raya Fisheries and Animal Husbandry Laboratory in November-December 2021. This research uses an experimental method with a Randomized Group Design (RAK). Factors tested are papain enzyme 3.25%, kale leaves 25% and taro leaves 25%, feed is given 3 times a day 3% of body weight (08.00 and 17.00 WIB) for 40 days. The results of ANOVA analysis (F test) showed that papain enzyme had a significant effect on weight growth and specific growth rate, feed conversion (P0.05). The results of the research show that treatment B obtained the best results on all parameters. The value of the survival rate was 86,89%, the specific growth rate was 1.93%/day, the feed conversion ratio was around 0.71, the water quality during the research temperature is around 26.8⁰C-27.5⁰C, pH is around 5.2-5.7 and DO is around 5.0 mg/L-7.8 mg/L. Therefore, it can be concluded that papain enzyme 3.25% is the best dose for gourami fish seeds. Keywords : Gourami fish, papain enzyme, additional feed